Application of flavonoid compounds suppresses the cotton aphid, Aphis gossypii - Zhang, Ying; Wang, Xinhang; Bian, Zhipeng; Se, Chenchen; Yang, Guoqing; Lu, Yanhui (Frontiers in Plant Science, 2025)
IntroductionThe cotton aphid Aphis gossypii is a significant polyphagous crop pest and has evolved a high level of resistance to neonicotinoids and other insecticides. Flavonoids, plant phytonutrients, have shown promise as natural insect deterrents and growth inhibitors. However, comprehensive evaluations of the effects of flavonoids on A. gossypii are currently lacking.MethodsIn this study, we first evaluated the effects of seven flavonoids (kaempferol, genistein, daidzein, naringenin, rutin, luteolin, and apigenin) on aphid settling behavior using choice assays, followed by electrical penetration graph (EPG) recordings to assess their influence on feeding activity. We then measured honeydew excretion and conducted life table analysis under laboratory conditions to assess effects on growth and reproduction. Under greenhouse conditions, all seven flavonoids were tested for their inhibitory effects on A. gossypii population growth over 12 days. Based on the results, three effective flavonoids were selected for further testing at four concentrations (1×, 2×, 3×, and 4× of 1 μg/μL) to assess dose-dependent effects.ResultsWe found that all seven flavonoids significantly deterred aphid settling on host plants. Kaempferol, daidzein, naringenin, rutin, luteolin, and apigenin significantly reduced the total duration of phloem feeding and the proportion of time spent on phloem-related activities. And also, each of seven flavonoids reduced honeydew production compared to controls. In the laboratory, all flavonoids reduced adult longevity and fecundity, and kaempferol, genistein, daidzein, naringenin, luteolin and apigenin also reduced the net reproductive rate (R0), intrinsic rate of increase (rm), and finite rate of increase (λ). Naringenin, apigenin, and kaempferol significantly inhibited A. gossypii population growth in a dose-dependent manner over 12 days.DiscussionThese results demonstrate that the seven flavonoids, especially naringenin, apigenin, and kaempferol tested provided effective management of A. gossypii populations by deterring host settling, reducing phloem feeding, honeydew production, and decreasing reproductive rates. This study highlights the potential of flavonoids as eco-friendly control agents against A. gossypii.